1975
DOI: 10.1111/j.1526-4610.1975.hed1502136.x
|View full text |Cite
|
Sign up to set email alerts
|

Concentration of Serotonin in Blood Platelets: Effect of Reserpine in Migraineurs

Abstract: SYNOPSIS Twenty‐three migraineurs and 7 controls were given intramuscular injections of reserpine. Platelets 5‐HT(serotonin) was measured 4–6 hours after injection and in migraineurs at weekly intervals for six weeks. Platelet 5‐HT fell to comparable levels in migraineurs and controls but 20 migraineurs had vascular headache within six hours after reserpine injection. No control had vascular headache after reserpine administration. Decreased platelet 5‐HT levels were found for 4–6 weeks after injection of rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

1976
1976
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
(6 reference statements)
0
5
0
Order By: Relevance
“…5‐hydroxytryptamine depletion induces migraine symptoms in humans 143 and migraineurs have been shown to have low serum and platelet 5‐HT levels between attacks 144,145 . Blood platelet and cerebrospinal fluid (CSF) levels of 5‐HT and its metabolites further decrease during a migraine attack, 144,145 which supports the hypothesis of a decrease in 5‐HT neuronal drive. Migraineurs have greater pain sensitivity in general, a symptom that has also been linked to changes in serotonergic neuronal systems originating in the NRM 138 .…”
mentioning
confidence: 97%
“…5‐hydroxytryptamine depletion induces migraine symptoms in humans 143 and migraineurs have been shown to have low serum and platelet 5‐HT levels between attacks 144,145 . Blood platelet and cerebrospinal fluid (CSF) levels of 5‐HT and its metabolites further decrease during a migraine attack, 144,145 which supports the hypothesis of a decrease in 5‐HT neuronal drive. Migraineurs have greater pain sensitivity in general, a symptom that has also been linked to changes in serotonergic neuronal systems originating in the NRM 138 .…”
mentioning
confidence: 97%
“…We also found that this small amount of reserpine causes low blood serotonin levels for at least 10 days in almost all patients; levels were still markedly depressed at 15 days in 3 patients, confirming another report. 15 We conclude that the extreme fall in blood serotonin levels associated with small amounts of parenteral reserpine is not usually associated with severe headache. The precipitation of migraine by other investigators using larger doses of reserpine could be due to biochemical or physiologic effects other than the effect of the drug on blood serotonin.…”
Section: Discussionmentioning
confidence: 71%
“…A notable finding is the tendency toward alleviation of headache at the end of the second and third days and despite the extreme falls in whole blood serotonin due to reserpine. The induction of migraine attacks by reserpine has been reported 4,14,15 although in one series this was inconsistent. It is assumed that these attacks are provoked by serotonin depletion by the drug.…”
Section: Discussionmentioning
confidence: 97%
“…During migraine attacks, increased release of serotonin from the storage granules of platelets and high amount of 5-HT metabolites in the urine samples have been reported (Genefke et al, 1975). In view of this, the effect of ST on platelet serotonin release using [ 14 C]5-HT was conducted in human platelets.…”
Section: Discussionmentioning
confidence: 98%